LA LLEGADA DE MARTA BRUNET A LA ARGENTINA (1939-1942): AUTOGESTIÓN Y ESTRATEGIAS DE INSTALACIÓN. - Carvajal-Muñoz, Osvaldo (Revista Chilena de Literatura, 2023)
Between 1939 and 1953 the Chilean writer Marta Brunet (1897-1967) was appointed as a diplomatic official in the cities of La Plata and Buenos Aires, Argentina. Literary historians and biographers of her time have diminished the relevance for her work of these years spent abroad, due to a supposed avant-garde influence. Such an influence supposedly marked the beginning of a second stage of her narrative production far from her early "criollismo". In this paper, the author's efforts and movements in the cultural field in the first half of the 20th century are reconstructed to access the relevance of her diplomatic stay in Argentina (1939-1942). Thus, based on an exhaustive archival work, this research identifies the strategies which allowed Marta Brunet to enter the Argentinian cultural field and expand her name and work to a continental dimension, this involves her collaboration with several newspapers and magazines, so as her relationship with the main cultural referents at the time.